Community medicine : a student's manual - Sanyal, Parikshit (Jaypee Brothers Medical Publishers, 2015)
Community medicine is the application of medical science to the society at large. It covers such diverse areas ranging from vaccination and control of epidemics to sanitation and town planning. This textbook is an attempt to present the subject of community medicine at a most introductory level to undergraduate medical students. It provides extensive but coverage on the concepts of health and disease and epidemiology. A solid conceptual foundation of biostatistics is provided. Major areas of community medicine, including communicable and noncommunicable disease, environmental health, mother and child's health, immunization, nutrition and national health programs are covered extensively. However, care has been taken as not to burden the memory of the student with irrelevant details at any point. As regarding style, the book takes the path less taken. Important definitions presented in an informal and simple manner emphasizing on keywords. Consistent use of highlight boxes improves the readability of the text and underline key facts. It is written in a manner akin to class notes, with a basic framework which every student can follow, while also providing additional material for the interested. The book is enriched with only the latest facts, figures and guidelines. Profusely illustrated both by original and public domain artwork and imagery, it is also a very pleasant read. In short, it is an introductory text to the fresher as well as a pre-exam review for the MBBS student.